Insights from immunoproteomic profiling of a rejected full-face transplant - Lee, Catherine A A; Wang, Diana; Kauke-Navarro, Martin; Russell-Goldman, Eleanor; Xu, Shuyun; Mucciarone, Kyla N; Sohrabi, Sadaf; Lian, Christine G; Pomahac, Bohdan; Murphy, George F (American journal of transplantation, 2023)
Vascularized composite allografts (VCAs) of faces and extremities are subject to chronic rejection that is incompletely understood. Here we report on immunoproteomic evaluation of a full facial VCA removed 88 months after transplantation due to chronic rejection. CD8-positive T cells of donor (graft) origin infiltrate deep intragraft arteries in apposition to degenerating endothelium of chimeric recipient origin in association with arteriosclerotic alterations. Digital spatial proteomic profiling highlighted proteins expressed by activated cytotoxic T cells and macrophages as well as pathway components involved in atherogenic responses, including Indoleamine 2,3-Dioxygenase 1 (IDO1) and Stimulator of Interferon Response CGAMP Interactor (STING). Chronic facial VCA rejection thus involves T cell/macrophage-mediated accelerated arteriosclerosis not normally represented in punch biopsies and potentially driven by persistent graft-resident effector T cells and recipient target endothelium that chimerically repopulates graft arteries.
Keywords: rejekce štěpu; Graft Survival; štěpy z kompozitní tkáně; Proteomics; Vascularized Composite Allotransplantation; Graft Rejection; proteomika; Facial Transplantation; Composite Tissue Allografts; přežívání štěpu; vaskularizovaná kompozitní alotransplantace; transplantace obličeje